Lactobacillus crispatus BC1 Biosurfactant Counteracts the Infectivity of Chlamydia trachomatis Elementary Bodies - Claudio Foschi; Carola Parolin; Barbara Giordani; Sara Morselli; Barbara Luppi; Beatrice Vitali; Antonella Marangoni (Microorganisms, 2021)
Lactobacilli-derived biosurfactants (BS) have shown promising effects as antimicrobial molecules. Since Lactobacillus crispatus plays a crucial role in maintaining vaginal eubiosis, BS from this species could represent novel therapeutic agents to counteract sexually transmitted pathogens, such as Chlamydia trachomatis (CT). The aim of the present study was to assess the inhibitory effects of a BS produced by the vaginal strain L. crispatus BC1 on the infectivity of CT elementary bodies (EBs). For concentrations ranging between 1 and 0.5 mg/mL at 60-min contact time, L. crispatus BC1 BS displayed a highly significant anti-CT activity, with about 50% reduction of EB infectivity towards HeLa cells. To identify the components responsible for chlamydial inhibition, a panel of selected fatty acids, including those present in BS lipopeptidic structure, was tested against CT EBs. Pentadecanoic acid, myristic acid, β-hydroxy-myristic acid, and β-hydroxy-palmitic acid were able to significantly reduce EBs infectivity up to 5–0.5 µg/mL, concentrations that resulted to be non-toxic for HeLa cells. These data can contribute to the understanding of the biological role of lactobacilli in the vaginal niche, as well as to promote the application of their produced BS as an innovative and antibiotic-sparing anti-chlamydial strategy.